Geomorphological and hydroclimatological characterization of the Pantanos de Centla Biosphere Reserve, Mexico - Medrano Pérez, Ojilve Ramón; Payano Almánzar, Reynaldo; López-Jiménez, Leonardo Noriel (Acta Universitaria, 2021)
In this article, the geomorphological and hydro climatological characterization of the Pantanos Centla Biosphere Reserve, Tabasco, Mexico, is shown. To that end, a digital database was generated with the reserve’s main characteristics (hydrology, climatology, hydrogeology, and other key aspects). The results show a system with little drainage capacity, influenced by the clay typology and an elongated morphology reflecting a long concentration time. The immediate challenge is the insufficient space-time data infrastructure which helps understand this natural area’s climatological and geological processes. Therefore, this contribution should impact decision-making within the natural area, based on the best available scientific information.